Pemanfaatan Instagram Sebagai Strategi Pemasaran Dalam Upaya Peningkatan Omzet Penjualan - Agustriana, Ajeng; Kirom, Novita Rifaul; Safitri, Cendy Eka; Kunizazila, Rahmadhila Raisyah Dwi; Kumalasari, Dwi; Rinda, Maria (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
With the increase in the number of business operators, there is an increasingly fierce competition in line with the swift flow of free trade that automatically makes competition come from all directions, both domestic, regional and global. There is no business, which is free to enjoy sales and profits, because there will be competition who want to enjoy it. The tight competition makes business people want to provide excellence and gain profits for business actors, for this reason, efforts are made in order to remain able to survive in the face of competition. Therefore, businesses must adapt themselves to the development of existing businesses. The results of this study conclude that the marketing strategy used by Himawari Collection applies a 5P marketing mix product (Product, Price, People, Promotion, Procsess). From these strategies found things in increasing sales turnover including paying attention to the use of Instagram, determining product strategies and prices in influencing consumer purchasing decisions, flexible prices, utilizing Instagram features to expand marketing targets, making it easier for consumers to make transactions, and stimulating consumers to make product purchases, guaranteeing safe products to consumers